Análise do crédito fundiário Banco da Terra: um estudo de caso no “assentamento” Agrovila Conde de Porto Alegre no município de São Borja/RS - Rabuske, Artênio Bernardo (2020)
The Agrarian Market Reform Model (MRAM) aimed to replace the redistributive agrarian reform model with a land purchase and sale model. The National Land Credit Program (PNCF) Banco da Terra (BT) made it possible for small family farmers, landowner or not, to pay for the land. The Banco da Terra Program was implemented in São Borja / RS in the early 2000s. This study aims to analyze the implementation of the BT Program in the municipality of São Borja / RS, at Agrovila Conde de Porto Alegre. The specific objectives includes, to point out the strengths and weaknesses of the BT Program, from the perspective of the public institutions participating in the process and the recipients themselves; to assess for any potential causes of attrition in the program. The research was characterized as a case study. Data collection was conducted via literature review, bibliographic research, on-site visits, and semi-structured interviews with the subjects involved between May and July 2020 were used. The results demonstrated that the Banco da Terra program was a viable public policy within the studied timeframe. However, over time, the implementation of this policy in Agrovila Conde de Porto Alegre did not present satisfactory results. Some aspects significantly limited the outcomes of the policy including lack of planning by the project's creators, distance [of recipients] from the urban center, and a lack of consistent monitoring through the involved institutions. Of the 25 beneficiaries placed at the beginning of the program, only 4 still remain.